Routledge handbook of public diplomacy [ - Snow, Nancy; Taylor, Philip M. (Routledge international handbooks, 2009)
Offers a comprehensive overview of the field of applied politics, encompassing political consulting, campaigns and elections, lobbying and advocacy, grass roots politics, fundraising, media and political communications, the role of the parties, political leadership, and the ethical dimensions of public life